Will Baker: capstone - Baker, Will, artist (Colorado State University. Libraries, 2026)
The artist's statement: I am an object maker and I think in bodies. I highlight the kinship between bodies; the body of a person, the body of a place, the body of an object. My work is an active recollection of the interconnectedness in our world. Themes of problem solving and relationship building are explored in objects of intimate scale. The goal is strengthening reciprocity with the world beyond the self. Metal lends itself as a material of connectivity. Movement between softness and hardness is the character of metal I choose to engage. Under the controlled action of a hammer, fluidity is exposed while rigidity is built. Metal is ushered through movement to a point of stillness. When enamel is fired onto metal the glass fuses and hardens but leaves the metal softened. At this point, metal becomes a delicate architecture, the glass surface acting as a fragile shelter. Bringing these states of being together, subtle complexities emerge among the constituencies of bodies. I am inspired by the mode and activation of memory. Moments that impress my mind to complete quiet become the measures of my memory. A body endures time and space by the oscillation between movement and stillness. I work to impart these sensate understandings into the objects I make, which offer a place for resting the mind or activating the body.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metals